Liver disease referrals to an urban, hospital‐based hepatology outpatient clinic over the past 25 years - Micah Grubert Van Iderstine; Daniel Iluz‐Freundlich; Casandra Dolovich; Eurielle Villarin; Gerald Y Minuk (JGH Open, 2020)
Background Additional hepatologists are required to manage the rapidly increasing number of patients with liver disease. One disincentive to trainees considering a career in hepatology is the longstanding perception that outpatient hepatology consists largely of managing patients with alcohol‐induced liver disease (ALD). Objectives To document the types of liver diseases and changes in liver disease referrals to an urban outpatient liver disease clinic over the past 25 years. Methods The nature of the liver disorder, age, gender, and socioeconomic status of patients referred to an urban, hospital‐based, liver diseases outpatient program were documented from 1992 to 2017. Joinpoint analysis was performed to identify significant trends in referral prevalence rates of various disorders. Results In 1992/1993, hepatitis C virus (HCV), followed by hepatitis B virus (HBV), “other”, non‐alcoholic fatty liver disease (NAFLD), and primary biliary cholangitis (PBC) were the most common underlying liver diseases in referred patients (39, 36, 12, 4.5, and 3.5% respectively), whereas in 2016/2017, NAFLD, HBV, HCV, “other,” and ALD were most common (60, 15, 12, 8.7, and 3.3%, respectively). Aside from NAFLD referrals, which consistently increased over the 25‐year period, the prevalence of all other liver disease referrals fluctuated but generally declined. Recently referred patients were significantly older (38 ± 13 years in 1992/1993 and 49 ± 15 years in 2016/2017, P < 0.0001), while gender and socioeconomic status have not changed. Conclusions Hepatology is a diverse, dynamic subspecialty where ALD continues to constitute less than 5% of all patient referrals.